CP-125 Evaluation of compliance and tolerability in treatment-naÏve patients suffering from idiopathic pulmonary fibrosis (IPF) and treated with pirfenidone. (24th March 2015) - Capano, F; Lerda, C; Bandelli, G; Filieri, A; Albera, C; Ielo, D
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a rare disease with significant morbidity and mortality, with a 18.07/1, 00, 000 prevalence in our Region. Pirfenidone is an orally administered antifibrotic approved for the treatment of mild-to-moderate IPF. 1 Pirfenidone is generally well tolerated, the most common side effects being on the gastro-intestinal (GI) tract and photosensitivity. However, side effects may partly offset treatment benefits and reduce compliance. Purpose: To assess side effects (tolerability) and compliance in (treatment-naïve) IPF patients receiving pirfenidone. Material and methods: In this prospective observational study, adherence was examined in patients treated between September 2013 and September 2014. Side effects and treatment compliance were recorded in a database. Adherence data were compared with the incidence of side effects occurring in the studied population. Results: 34 IPF patients were evaluated during a 12 month follow-up. Comparison between prescribing and dispensing data showed that 19 (56%) of patients received 100% of the prescribed treatment, 22 (65%) received more than 90%, and only 3 (9%) received less than 50%. Side effects led to only 15% of patients discontinuing pirfenidone and were more evident during the first six months of treatment, as observed in clinical trials. Conclusion: Tolerability: most side effects were manageable with supportive measures. Compliance: overall it was good. Closer pharmacist/physician interaction could further improve patient compliance. References and/or Acknowledgements: 1 EMA summary of product characteristics No conflict of interest.